Uji Anti Virus Senyawa Kurkumin dan PGV-0 pada Virus Dengue-2 dengan RT-PCR - Dewi Marbawati; Siti Rahmah Umniyati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Treatment of Dengue patients today are to relieve symptoms because specific therapies and effective anti-viral drugs have not been found. Curcumin is known has anti-viral activity, anti-inflammatory, anti-oxidant, anti-parasitic and anti-cancer. Curcumin has a weakness that is sensitive to acidity (pH) and light, so curcumin analogues that ispentagamavunon-0 (PGV-0) was made in order to obtain better anti viral activity. The purpose of this study was to determine the effect of curcumin and PGV-0 on vero cells infected by Dengue-2. This research was conducted in the laboratory of parasitology Faculty of Medicine of Gadjah Mada University in January-September 2013. Experimental studies using RT-PCR test to determine the presence of Dengue-2 antigen. Dengue-2 virus propagated in C636 cellsand then infected in vero cells to further treated with curcumin and PGV-0. The incubation period of Dengue-2 infections performed for 1 and 3 days. The results of RT-PCR showed Dengue-2 antigen was seen in the 3-day infection period in the treatment of curcumin. This result indicates PGV-0 has potential antiviral better than curcumin.